PENEGAKAN HUKUM TERHADAP PRAKTIK TENEGA KESEHATAN TANPA IZIN BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2014 TENTANG TENAGA KESEHATAN DI KOTA PEKANBARU - Handayanis, Okta Dwi; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The practice of unlicensed health workers is one of the crimes that harm the entire community, especially the health needs of the community to make the risk of the existence of health workers practice without this permit will increasingly endanger the safety of the community. In practice, health workers should be continuously upgraded through continuous education and training, certification, registration, licensing, as well as guidance, supervision and monitoring so that the implementation of health personnel practices is in accordance with the development of science and technology. The aim of this thesis are: First, the enforcement of the law against the practice of medical personnel without permission under Act No. 36 of 2014 on Health Workers in Pekanbaru, Second, obstacles to the enforcement of the law against the practice of medical personnel without permission under Act No. 36 of 2014 Health workers in the city of Pekanbaru, Third, efforts are being made to overcome the barriers in law enforcement against unlicensed practice of health professionals based on Law No. 36 Year 2014 about Health workers in Pekanbaru.This research type is research of sociological law, that is research with see effectiveness of law enforcement in field. This research was conducted at Pekanbaru Police Resort and Pekanbaru City Health Office. Population and sample are all parties related to the problem under study. Sources of data used are: primary data, secondary data and tertiary data, data collection techniques using interviews and literature review.From the results of research there are three main issues that can be concluded. First, the enforcement of the law against the practice of health workers without permits in the city of Pekanbaru, the lack of coordination between the Parties to the Police, the Department of Health and the Indonesian Dentists Association, Second, obstacles to the enforcement of the law against the practice of medical personnel without permission in Pekanbaru, Factors Act, factors of law enforcement officers, the factor of facilities and amenities, as well as community factors as the most vital, Third, efforts are being made to overcome the obstacles in the enforcement of laws against the practice of medical personnel without permission in Pekanbaru, law enforcement officers are expected to cooperate with agencies that have Supervisory authority and supervision and guidance in the form of socialization to the community related to the knowledge about the practice of health workers without permission and danger from visiting the practice of health workers without permission. Suggestions writer, First, role of government oversight associated with the practice of health workers without such permission must first be improved to avoid the occurrence of violations, Second, law enforcement officials are expected to work closely with the Department of Health and the Association of Indonesian Your doctor. The health offices are more effective in monitoring the practice of unskilled health workers.Keywords: Law Enforcement - Health Worker Practices - Without Permission